Proceedings of the 8th ACM International Conference on Embedded Software 2008
DOI: 10.1145/1450058.1450084
|View full text |Cite
|
Sign up to set email alerts
|

A generalized static data flow clustering algorithm for mpsoc scheduling of multimedia applications

Abstract: In this paper, we propose a generalized clustering approach for static data flow subgraphs mapped onto individual processors in Multi-Processor System on Chips (MPSoCs). The goal of clustering is to replace the static data flow subgraph by a single dynamic data flow actor such that the global performance in terms of latency and throughput is optimized. Through our proposed clustering approach, the scheduling of connected static data flow subgraphs can be coordinated with enclosing system representations in a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 18 publications
0
40
0
Order By: Relevance
“…We illustrate this by example. Note that in [4] it is also observed that CSDF is not a sufficient abstraction of composite SDF models, however, the example used in that paper embeds a composite SDF graph into a dynamic data flow model. Therefore the overall model is not strictly SDF.…”
Section: Discussion: Inadequacy Of Cyclo-static Data Flowmentioning
confidence: 99%
See 4 more Smart Citations
“…We illustrate this by example. Note that in [4] it is also observed that CSDF is not a sufficient abstraction of composite SDF models, however, the example used in that paper embeds a composite SDF graph into a dynamic data flow model. Therefore the overall model is not strictly SDF.…”
Section: Discussion: Inadequacy Of Cyclo-static Data Flowmentioning
confidence: 99%
“…This model captures the SDF model given in Figure 3 of [4]. Actor A2 is a composite actor designed so as to consume 2 tokens on each of its input ports and produce 2 tokens on each of its output ports every time it fires.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations